Kerjasama Guru dan Orang Tua dalam Mengatasi Masalah Belajar Anak SD di Kasik Putih, Kec Sungai Aur, Kabupaten Pasaman Barat - Utari, Silfia; Alimir, Alimir; Jasmienti, Jasmienti; Supriadi, Supriadi (Lembaga Yasin AlSys, 2023)
The research is motivated by problems that occur with elementary school children related to children's learning problems, the learning problems here are: there are still children who do not understand learning, and there are children who while studying do activities such as disturbing friends in class, and do not pay attention to the teacher in learning, as well as related to parental concern. This study aims to reveal the form of cooperation between teachers and parents in overcoming the learning problems of elementary school children in Kasik Putih, Sungai Aur District, West Pasaman Regency. This study uses a qualitative descriptive methodological approach, namely field research (field research) is a method that describes the conditions that occur in the field. Located at SDN 07 Sungai Aur, the data source for this research is the collaboration of teachers and parents. Key informants 2 teachers and 2 parents, supporting informants 2 children, were able to provide information in accordance with the research data. Data collection techniques carried out by researchers were field observations, interviews, documentation, data analysis techniques, data reduction, data presentation and drawing conclusions. While the data validity technique uses data trigulation techniques. In this research data trigulation the authors use the point of comparing observational data with interviews. The results of the study concluded: 1) the form of teacher and parent collaboration in overcoming children's learning problems is communication between the two parties, supervising children's learning at school and at home, supervising children's behavior at school and at home. Efforts made to establish teacher and parent collaboration are visits to parents' homes, correspondence, being invited to school, joint meetings, and division of tasks.-day.